2009
DOI: 10.5688/aj730108
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Geographical Factors and the Presence of Advanced Community Pharmacy Practice Sites in Greater Chicago

Abstract: Objectives. To determine the availability of experiential learning opportunities in culturally diverse areas and to identify opportunities and barriers to attract and sustain sites for the University of Illinois at Chicago College of Pharmacy. Methods. Utilizing variables of census tract income, racial/ethnicity composition and crime index, data analyses included descriptive statistics and multivariate logistic regression. Faculty members involved in experiential education were interviewed to identify other fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Also related to this, the findings of another US study[15] determined, among other things, the availability of experiential learning opportunities in culturally diverse areas. The paper argues that exposure to diverse populations during advanced community practice experiences has parallels with the strategic college objectives of expanding and diversifying experiential sites to enhance pharmacy students’ abilities to meet emerging patient‐care challenges and opportunities.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Also related to this, the findings of another US study[15] determined, among other things, the availability of experiential learning opportunities in culturally diverse areas. The paper argues that exposure to diverse populations during advanced community practice experiences has parallels with the strategic college objectives of expanding and diversifying experiential sites to enhance pharmacy students’ abilities to meet emerging patient‐care challenges and opportunities.…”
Section: Resultsmentioning
confidence: 87%
“…While majority of the identified papers originated from the USA (21, 58.3%), there was a significant gap in the UK evidence base (seven papers, 19.4%), particularly for those themes where no UK papers were identified (see Table ; for definition of categories, see Table ). In terms of the composition of the empirical studies, it was noticed that majority of the identified papers used a quantitative approach in their study, while only three papers (8.3%) used a mixed‐method approach [13–15]. There was also a significant gap in the quality of evidence of the papers reviewed – only one literature review study was identified [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional didactic lectures are often viewed as a “sage on the stage method” because they are teacher- centered, and students are passive recipients of information ( 2 ). As such, the traditional didactic lecture approach has long been criticized for its inability to stimulate deep learning and knowledge acquisition ( 3 – 6 ). Despite these criticisms, a review of the roles of lectures in higher education revealed that lectures are still an important and relevant teaching method, particularly because they offer meaningful benefits, including pedagogical (i.e., content framework of a subject), practical (i.e., listening and notetaking skills), and social (i.e., cost effective and shared communal understanding) in nature ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…49 A common example of mixed methods research in pharmacy education involves the use of qualitative data from focus groups or interviews to triangulate or provide further insight into findings from surveys, data models, or questionnaires. 50,51 …”
Section: Mixed Methods Researchmentioning
confidence: 99%